TATWIRUL MAWAD AD DIRASIYAH ALA KITAB "BAHASA ARAB MTS KELAS VII” - Hendra Setiawan (Jurnal Al-Maqoyis, 2019)
Arabic learning is a process of providing science and knowledge about elements of Arabic and Arabic-speaking skills to students. In giving material to students there is a crucial concern for material to be fully delivered these are the application of learning methods, the use of media and evaluation in Arabic learning. The teaching materials are essential in the process of learning Arabic. Therefore, the teaching learning process requires motivational drives in order to increase the competence of student language. The purpose of developing teaching materials in the study was for teaching materials to be used to be more systematic and in accordance with student development. The methods used in this study are Research and Development. The developed book is an Arabic book for Madrasah Tsanawiyah under the title “Bahasa Arab Madrasah Tsanawiyah Class VII. This research has only come to material development. The result of this study was the addition of material, changing material, changing material composition as well as adding methods in its teaching.